FAKTOR-FAKTOR YANG MEMPENGARUHI PERILAKU KONSUMTIF PADA GENERASI MILLENIAL PENGGUNA SHOPEE DI SOLO - Atmaja, Ria Melina; Susanti, Ari (Jurnal Akuntansi dan Bisnis, 2022)
The development of technology has a big impact and provides convenience for its users. However, it also has an impact with the increase in Consumptive Behavior in millennials. The purpose of the study was to find out the influence of Lifestyle variable on Consumptive Behavior variable, Financial Literacy variable on Consumptive Behavior variable, Financial Attitude variable to Consumptive Behavior variable, and Financial Behavior variable on Consumptive Behavior variable. The population in this study was Millennials in Solo with an age range of 18- 24 years and a sample taken as many as 100 respondents. Nonprobability sampling techniques there are various types, therefore researchers choose the way purposive random sampling. To analyze data using data instrument test methods, classical assumption tests and multiple regression analysis with the help of IBM SPSS Statistic 26 program. The results of the study showed that lifestyle has a significant effect on consumptive behavior. And Financial Attitude has a significant effect on consumptive behavior. While the results of the study showed that Financal Literacy and Financal Behavior affect not significant on Consumptive Behavior.Keywords: Lifestyle, Financial Literacy, Financial Attitude, Financial Behavior and Consumptive  Behavior.